Long-term (up to 4.5 years) treatment with fingolimod in multiple sclerosis: results from the extension of the randomised TRANSFORMS study - Cohen, Jeffrey A (J Neurol Neurosurg Psychiatry, 2016)
OBJECTIVE: The 12-month (M), phase 3, double-blind, randomised TRANSFORMS study demonstrated significant benefits of fingolimod 0.5 or 1.25 mg over interferon β-1a (IFNβ-1a) in patients with relapsing–remitting multiple sclerosis. We report the results of long-term (up to 4.5 years) extension of TRANSFORMS. METHODS: Patients randomised to fingolimod (0.5/1.25 mg) in the core phase continued the same dose (continuous-fingolimod) in the extension, whereas those on IFNβ-1a were re-randomised (1:1) to fingolimod (IFN-switch; IFN: 0.5/1.25 mg). Outcomes included annualised relapse rate (ARR), confirmed disability progression and MRI measures. Results are presented here for the continuous-fingolimod 0.5 mg and pooled IFN-switch groups. RESULTS: Of the 1027 patients who entered the extension, 772 (75.2%) completed the study. From baseline to the end of the study (EOS), ARR in patients on continuous-fingolimod 0.5 mg was significantly lower than in the IFN-switch group (M0–EOS: 0.17 vs 0.27). After switching to fingolimod (M0–12 vs M13–EOS), patients initially treated with IFN had a 50% reduction in ARR (0.40 vs 0.20), reduced MRI activity and a lower rate of brain volume loss. In a post hoc analysis, the proportion of IFN-switch patients with no evidence of disease activity increased by approximately 50% in the first year after switching to fingolimod treatment (44.3% to 66.0%). The safety profile was consistent with that observed in the core phase. CONCLUSIONS: These results support a continued effect of long-term fingolimod therapy in maintaining a low rate of disease activity and sustained improved efficacy after switching from IFNβ-1a to fingolimod. CLINICAL TRIAL REGISTRATION NO: NCT00340834.